Numerical Structural Analysis of Main Landing Gear System Using ANSYS - Hesham Mraied; Khadeejah Altoumi (African Journal of Advanced Pure and Applied Sciences, 2026)
The structural analysis of titanium (Ti) and aluminum (Al) alloys was conducted using ANSYS. The analysis studied the mechanical properties of these alloys including deformation, stress and strain characteristics under operational loads. The analysis showed that the total deformation of Ti Alloy (2.33 mm) is smaller than that of Al alloy (3.66 mm), indicating that the former alloy exhibited higher structural stability and lower susceptibility to yielding. It was also found that both alloys experienced similar maximum principal stresses of ~23MPa. Moreover, the uniform stress distribution observed for both alloys indicated structural stability and reduced suitability to localized failure. Both Von Mises and principal stress analysis, confirmed the high strength of the alloys under tensile and compressive loads. The equivalent elastic strain of Ti alloy (0.2 mm/mm) is smaller than that of Al alloy (0.3 mm/mm), which is in agreement with the elastic moduli of both alloys. These results confirm that Ti alloy is suitable for critical aerospace applications where high strengths, reduced deformations and high resistance to fatigue are required. Due to its higher energy absorption and deformation, Al alloy was found to be more suitable for applications where energy dissipation is more desirable compared to structural rigidity. Finally, the structural analysis revealed the importance of material selection in aerospace engineering based on specific performance and safety regulations.